DETERMINATION OF THE BIOSOLAR QUALITY BY ANALYSIS - Nurdianti Nurdin (Marina Chimica Acta, 2016)
Research on biodiesel quality through the analysis of trace elements concentrations using Inductively Coupled Plasma Optical Emission Spectrometry (ICP OES) resulting from commercial biodiesel and of various formulations of blending between biodiesel from palm oil with diesel oil has been done. The study begins with the manufacture of biodiesel through a process of esterification and transesterification reaction with methanol, biodiesel quality analysis, and manufacturing of biodiesel at various blending namely B5, B10, B15, B20, and B25. Trace elements analysis was performed using Inductively Coupled Plasma Optical Emission Spectrometry (ICP OES). The research found concentration of trace elements in commercial biodiesel A and commercial biodiesel B dominated by K of 10.68 mg/L and 9,424 mg/L, followed by Mg, Na, Ca, and Fe. Most trace elements in biodiesel B5 is K amounted to 5.846 mg/L, followed by Na, Mg, Ca, and U. Trace elements are most in biodiesel B10 K of 7.113 mg/L, followed by U, Na, Mg, Fe and Ca. Most trace elements in biodiesel B15 is Na amounted to 35.89 mg/L, followed by Fe and Mg. Most trace elements in biodiesel B20 is K amounted to 7.154 mg/L, followed by Na, Ca, Mg, and Fe. Most trace elements in biodiesel B25 is K amounted to 6.154 mg/L, followed by Na, Ca, Mg, and Fe.Keywords: Biodiesel, ICP OES (Inductively Coupled Plasma